1997
DOI: 10.1007/s002239900314
|View full text |Cite
|
Sign up to set email alerts
|

Clodronate Prevents Bone Loss in Aged Ovariectomized Rats

Abstract: The purpose of this study was to investigate the ability of clodronate to prevent ovariectomy (OVX)-induced osteopenia in aged rats. Fourteen-month-old female Sprague-Dawley rats (n = 166) were randomized into six groups. One group was sacrificed at the start of the study, four groups were ovariectomized, and one group was sham-operated (Sham). The OVX rats were given subcutaneously either vehicle (veh) or clodronate at doses of 3, 7, or 25 mg/kg once a week for 3 months, and the Sham rats were given the vehic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
6
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
4
6
0
Order By: Relevance
“…Daily oral clodronate treatment depressed the OVX‐induced increase in bone turnover as evidenced by decreased values of urinary excretion of deoxypyridinoline/creatinine and serum osteocalcin. Similar findings were made previously with comparable subcutaneous doses given once a week (22,24,25) . In addition, the high dose of clodronate inhibited the increase in the activity of serum S‐ALP.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Daily oral clodronate treatment depressed the OVX‐induced increase in bone turnover as evidenced by decreased values of urinary excretion of deoxypyridinoline/creatinine and serum osteocalcin. Similar findings were made previously with comparable subcutaneous doses given once a week (22,24,25) . In addition, the high dose of clodronate inhibited the increase in the activity of serum S‐ALP.…”
Section: Discussionsupporting
confidence: 88%
“…Longitudinal 5‐μm‐thick sections were cut with a Polycut S heavy‐duty microtome (Leica Instruments GmbH, Heidelberg, Germany) from the femoral neck at two levels spaced 100 μm apart, and the sections were stained by the von Kossa method with hematoxylin/McNeal's tetrachrome counterstain (26) . Twenty‐micrometer‐thick microground femoral mid‐diaphyseal cross‐sections were processed as described previously (22,25) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to our study, there are data showing that distinct bisphosphonates are able to prevent trabecular osteopenia in ovariectomy, a classical experimental model of osteoporosis (13,30). These studies observed improvement in the ultimate force for bone fracture only in lumbar spine bone and, similar to our results, no effect was verified in long bones of animals subjected to bisphosphonate treatment (13,30,31). Kippo et al (31) suggested that in the rat the amount of cortical bone and external bone dimensions would contribute more to the structural strength of the femur than the amount and microarchitecture of trabecular bone.…”
Section: Discussionsupporting
confidence: 89%
“…These studies observed improvement in the ultimate force for bone fracture only in lumbar spine bone and, similar to our results, no effect was verified in long bones of animals subjected to bisphosphonate treatment (13,30,31). Kippo et al (31) suggested that in the rat the amount of cortical bone and external bone dimensions would contribute more to the structural strength of the femur than the amount and microarchitecture of trabecular bone. In addition to those studies, the present investigation showed that pamidronate used as preventive treatment may impair bone strength in rats submitted to surgically induced cholestasis.…”
Section: Discussionsupporting
confidence: 89%